Carregando a literatura nas costas: a obra de Júlio Damásio - Lopes, Júlia Cristina Ramos (2012)
The idea of this research came with the importance of the marginal literature, and also the formation of new readers. Looking to present the difficulties that the marginals writers found to establish. Working with two different contexts, the historical genesis of the artist, putting himself at the border of the system, revealed the relation between the market and the present time, showed here by the storyteller Julio Damasio, independent writer and autodidact, born in 1966, besides his independent publishing of his books, gives lectures and workshops in public schools of Parana.